Tanggung Jawab Hukum Pemerintah Atas Pemenuhan Hak Laktasi Bagi Tenaga Kesehatan di Fasilitas Pelayanan Kesehatan - Nurlaela, Wiwik; Noor, M. Tauchid; Nugraheni, Ninis (Jurnal Hukum dan Etika Kesehatan, 2023)
The right to lactation is part of human rights that naturally belongs to a woman, including female health workers who are protected by the state.In carrying out their duty to fulfill the rights of patients, they often face conflicts with the fulfillment of lactation rights that they should get. As a legal country, Indonesia provides protection for the fulfillment of lactation rights in several lawsand regulations. This study uses the type of normative juridical law research, namely library law research, with statutory approaches, and conceptual. The problems and objectives of this study are to analyze the conflict between the lactation rights of health workers and the rights of patients in health services and the government's legal responsibility for fulfilling the rights of lactation for health workers. The results showed that the biggest clashes experienced by health workers in fulfilling lactation rights was as welthe disharmony of laws and regulations between the Labor Law or the Job Creation Law and the Government Employees Management Government Regulations with the Health Law and the Government Regulationson Exclusive Breastfeeding. The government is responsible for fulfilling the right to lactation. The government can be seen as a legal subject and legal object, which means that the government supervises as well as was upervised the implementation of the provisions for fulfilling the right to lactation for health workers.